Transnational Cultural Capital and Career Mobility among Vocational High School Graduates in Japanese Companies - Wahyu Handayani Setyaningsih; Lufi Wahidati; Fatmawati Djafri (Bulletin of Social Studies and Community Development, 2026)
This study examines how Japanese-related cultural capital shapes the career mobility of vocational high school graduates employed in Japanese companies in Indonesia. This study employed a qualitative research design. Prior to the main fieldwork, a preliminary organizational survey was conducted to identify companies willing to participate and to recruit suitable interview participants. The primary data were generated through semi-structured interviews with five purposively selected employees working at Japanese companies in the KIIC area of West Java. The interview data were analyzed thematically using Pierre Bourdieu’s concepts of cultural capital, field, and symbolic capital as analytical lenses. The findings reveal that internship experience in Japan serves as transnational cultural capital, enabling workers to acquire workplace dispositions, Japanese-language proficiency, and familiarity with Japanese organizational practices. Furthermore, JLPT certification operates as institutionalized cultural capital that legitimizes these competencies and facilitates their conversion into symbolic recognition, career advancement, and economic opportunities. The study also shows that unequal access to internship opportunities and Japanese language certification contributes to differentiated career trajectories among employees. These findings highlight the importance of expanding equitable access to Japanese-related cultural capital through vocational education and stronger collaboration between vocational schools and Japanese companies to promote more inclusive career mobility. Keywords: Career mobility, Japanese companies, Transnational cultural capital, Vocational high school graduates.